2017
DOI: 10.1016/j.tranon.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Stromal and Tumor Expression of ROR1 and ROR2 in Histological Subtypes of Epithelial Ovarian Cancer

Abstract: OBJECTIVE: The ROR1 and ROR2 receptor tyrosine kinases have both been implicated in ovarian cancer progression and have been shown to drive migration and invasion. There is an increasing importance of the role of stroma in ovarian cancer metastasis; however, neither ROR1 nor ROR2 expression in tumor or stromal cells has been analyzed in the same clinical cohort. AIM: To determine ROR1 and ROR2 expression in ovarian cancer and surrounding microenvironment and examine associations with clinicopathological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…Thus, Ror2 exhibits either tumor‐promotive or tumor‐suppressive function depending on the type of tumors. Furthermore, Ror2 is expressed in not only tumor cells but also tumor stroma, and high Ror2 expression in tumor stroma is associated with poor prognosis in ovarian cancer and pancreatic ductal adenocarcinoma, suggesting that tumor progression can be promoted by Ror2‐mediated signaling in either tumor cells themselves or tumor stromal cells through tumor stroma interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Ror2 exhibits either tumor‐promotive or tumor‐suppressive function depending on the type of tumors. Furthermore, Ror2 is expressed in not only tumor cells but also tumor stroma, and high Ror2 expression in tumor stroma is associated with poor prognosis in ovarian cancer and pancreatic ductal adenocarcinoma, suggesting that tumor progression can be promoted by Ror2‐mediated signaling in either tumor cells themselves or tumor stromal cells through tumor stroma interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Ror2 and Wnt5a are highly expressed in various types of cancer cells, resulting in constitutive activation of Wnt5a‐Ror2 signaling in a cell‐autonomous manner, eventually contributing to tumor progression . However, expression of Ror2 is also observed in cellular components of tumor stroma, and higher levels of Ror2 expression in tumor stroma seem to be associated with poor prognosis in ovarian cancer and pancreatic ductal adenocarcinoma, suggesting an important role of stromal Ror2 in tumor progression. We have previously shown that MSC express both Wnt5a and Ror2, even though Wnt5a‐Ror2 signaling in MSC seems not to affect proliferation and viability of themselves .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, we have demonstrated (Henry et al 2016) that overexpression of both RORs results in increased invasion, while their knockdown inhibits migration and invasion and sensitises chemotherapy resistant cell lines to cisplatin in ovarian cancer. In a cohort of 178 patient samples with matched benign, primary and metastatic lesions, both receptors were abnormally expressed in both epithelium and stroma -ROR2 most prominently in early stage, low-grade endometrioid ovarian tumours and in the stroma of the serous subtype (Henry et al 2017). Therefore there is evidence for the potential of ROR1 and ROR2 as therapeutic targets in the related endometrial tumours.…”
Section: Rors and Endometrial Cancermentioning
confidence: 99%
“…We previously found ROR2, but not ROR1 upregulation in ovarian cancer associated stroma, in particular in metastatic samples of matched patient study cases [ 12 ]. ROR2 expression in stroma has otherwise only been reported in pancreatic cancer [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results were then supported in a chemoresistant cell line model [ 9 ], and by other studies using in vivo xenografts, where a ROR1 monoclonal inhibitor significantly decreased tumour burden [ 10 , 11 ]. We recently identified an upregulation of ROR2 in stromal compartments of tissue samples from patients with metastatic disease [ 12 ]. Here we aimed to further investigate the role of these receptors in tumour and stroma, in the setting of omental metastasis using a patient derived organotypic model.…”
Section: Introductionmentioning
confidence: 99%